2004
DOI: 10.1074/jbc.m312918200
|View full text |Cite
|
Sign up to set email alerts
|

Newly Discovered Neutral Glycosphingolipids in Aureobasidin A-resistant Zygomycetes

Abstract: We found for the first time that Zygomycetes species showed resistance to Aureobasidin A, an antifungal agent. A novel family of neutral glycosphingolipids (GSLs) was found in these fungi and isolated from Mucor hiemalis, which is a typical Zygomycetes species. Their structures were completely determined by compositional sugar, fatty acid, and sphingoid analyses, methylation analysis, matrix-assisted laser desorption ionization time-of-flight/mass spectrometry, and 1 H NMR spectroscopy. They were as follows: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In this research we found more radiolabeled triand tetra-saccharylceramide than mono-and disaccharylceramide, and this tendency closely resembled the synthetic pattern of the neogala-series saccharylceramide (Aoki et al, 2004), supporting our assumption.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this research we found more radiolabeled triand tetra-saccharylceramide than mono-and disaccharylceramide, and this tendency closely resembled the synthetic pattern of the neogala-series saccharylceramide (Aoki et al, 2004), supporting our assumption.…”
Section: Discussionsupporting
confidence: 77%
“…These saccharides were specifically found in flatworms, platheliminthes, such as tapeworm and round worm, and in annelida, such as earthworms (Dennis et al, 1992;Hada et al, 2001). Recently, however, these oligosaccharides were also discovered in zygomycetes such as Rhizopus (Aoki et al, 2004) and thus they are much more widely distributed than had originally been thought. To our knowledge, there is no report showing the neogala-series saccharylceramide in lepidopteran insects, but as mentioned above, it is not surprising that they exist in insects.…”
Section: Discussionmentioning
confidence: 96%
“…These include 9-Me d18:2-h16:0 and 9-Me d18:2-h18:0, which have been reported to be a major ceramide moiety of CMS from fungi, [26][27][28][29] and 9-Me d18:2-h18:1, which was found in Sporothrix schenckii and Histoplasma capsulatum by Tolendo et al 30,31) Aoki et al reported that Zygomycetes species produce a new group of neutral GSLs with 1-6 or 1-6 galactoside linked to phytoceramides instead of glycosylinositolphosphoceramide, which was found in all fungi, although the CMS detected was GlcCer (9-Me d18:2-h16:0). 32) By observation of glycolipid patterns in activated sludge monthly through 1 year, we noticed that high polar GSLs assumed to possess the oligosaccharide chain tended to increase in the cold period. Such GSLs are not prevalent in fungi, except for Zygomycetes, as reported by Aoki et al, 32) and Mucor sp.…”
Section: Discussionmentioning
confidence: 99%
“…32) By observation of glycolipid patterns in activated sludge monthly through 1 year, we noticed that high polar GSLs assumed to possess the oligosaccharide chain tended to increase in the cold period. Such GSLs are not prevalent in fungi, except for Zygomycetes, as reported by Aoki et al, 32) and Mucor sp. was isolated from activated sludge collected in January, but not from sludge in May in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…After removing the acid by evaporation under a nitrogen stream, the hydrolyzates, containing both monosaccharide alditols (original reduc-ing terminus) and monosaccharide aldoses (internal and nonreducing terminal residues), were acetylated with 0.5 ml of pyridine:acetic anhydride (1:1 (v/v)) at 100°C for 10 min (54). The resulting monosaccharide aldose and alditol acetates were analyzed by gas chromatographymass spectrometry (GC-MS; see below for conditions).…”
Section: Identification Of Reducing Terminal Monosaccharides and Monomentioning
confidence: 99%